2021
DOI: 10.1002/iid3.550
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinical characteristics among different age group of adult COVID‐19 patients: A multicenter study

Abstract: Background Coronavirus disease (COVID‐19) is a global infectious disease with a large burden of illness and high health care costs. This study aimed to compare clinical features among adult COVID‐19 patients in different age groups. Methods Laboratory‐confirmed adult COVID‐19 infection cases between December 31, 2019 to March 8, 2020 obtained from Neighboring Cities. Patients were divided into five age groups. Clinical characteristics were compared among different age g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Access focused on health care providers and residents of long‐term care facilities (phase 1a) 5 . Because of the increased risk of serious complications for older adults, 6–8 the Centers for Disease Control and Prevention updated allocation guidelines in late December 2021 to include all people aged 75 years and older in phase 1b. Phase 1c included all people aged 65–74 years and those aged 16–64 years who had high‐risk medical conditions 5 …”
Section: Introductionmentioning
confidence: 99%
“…Access focused on health care providers and residents of long‐term care facilities (phase 1a) 5 . Because of the increased risk of serious complications for older adults, 6–8 the Centers for Disease Control and Prevention updated allocation guidelines in late December 2021 to include all people aged 75 years and older in phase 1b. Phase 1c included all people aged 65–74 years and those aged 16–64 years who had high‐risk medical conditions 5 …”
Section: Introductionmentioning
confidence: 99%
“…The higher rate of poor outcomes in patients with comorbidities suggests that the presence of comorbidities is associated with an increased risk and frequent exacerbation of infection. [21][22][23] Additionally, the mortality rate was 4.9% in our hospitalized patients. No significant difference was found in the mortality rate between fully vaccinated and unvaccinated patients in this study.…”
Section: Discussionmentioning
confidence: 59%
“…Besides, our findings did not indicate any significant difference in terms of poor outcomes between younger and older hospitalized patients. The higher rate of poor outcomes in patients with comorbidities suggests that the presence of comorbidities is associated with an increased risk and frequent exacerbation of infection 21–23 . Additionally, the mortality rate was 4.9% in our hospitalized patients.…”
Section: Discussionmentioning
confidence: 70%
“…Cheng et al reported one-third of participants had one or more chronic diseases in laboratory-confirmed adult COVID-19 infection cases. In their study, patients with a severe or critical type of COVID-19 disease were more likely to have accompanying chronic health issues, including DM, hypertension, chronic heart disease, and chronic pulmonary disease, than a mild or moderate type of COVID-19 disease (27). In a study consisting of COVID-19 confirmed cases followed-by primary healthcare services, 25.4% of the patients had a chronic disease including hypertension (16.8%) and diabetes mellitus (7.0%) (18).…”
Section: Comorbiditiesmentioning
confidence: 94%